Social Determinants of Health and Patient-reported Outcomes Following Autologous Breast Reconstruction, Using Insurance as a Proxy - Plotsker, Ethan L.; Graziano, Francis D.; Kim, Minji; Boe, Lillian A.; Tadros, Audree B.; Matros, Evan; Azoury, Said C.; Nelson, Jonas A. (Journal of Reconstructive Microsurgery, 2024)
Background Insurance type can serve as a surrogate marker for social determinants of health and can influence many aspects of the breast reconstruction experience. We aimed to examine the impact of insurance coverage on patients reported outcomes with the BREAST-Q (patient reported outcome measure for breast reconstruction patients, in patients receiving) in patients receiving deep inferior epigastric artery perforator (DIEP) flap breast reconstruction.Methods We retrospectively examined patients who received DIEP flaps at our institution from 2010 to 2019. Patients were divided into categories by insurance: commercial, Medicaid, or Medicare. Demographic factors, surgical factors, and complication data were recorded. Descriptive statistics, Fisher's exact, Kruskal–Wallis rank sum tests, and generalized estimating equations were performed to identify associations between insurance status and five domains of the BREAST-Q Reconstructive module.Results A total of 1,285 patients were included, of which 1,011 (78.7%) had commercial, 89 (6.9%) had Medicaid, and 185 (14.4%) had Medicare insurances. Total flap loss rates were significantly higher in the Medicare and Medicaid patients as compared to commercial patients; however, commercial patients had a higher rate of wound dehiscence as compared to Medicare patients. With all other factors controlled for, patients with Medicare had lower Physical Well-being of the Chest (PWBC) than patients with commercial insurance (β = − 3.1, 95% confidence interval (CI): −5.0, −1.2, p = 0.002). There were no significant associations between insurance classification and other domains of the BREAST-Q.Conclusion Patients with government-issued insurance had lower success rates of autologous breast reconstruction. Further, patients with Medicare had lower PWBC than patients with commercial insurance regardless of other factors, while other BREAST-Q metrics did not differ. Further investigation as to the causes of such variation is warranted in larger, more diverse cohorts.
Keywords: social determinants of health; insurance; disparities; breast; autologous; DIEP